Identification of Novel Loci and Candidate Genes for Cucumber Downy Mildew Resistance Using GWAS - Liu, Xiaoping (Plants (Basel), 2020)
Downy mildew (DM) is one of the most serious diseases in cucumber. Multiple quantitative trait loci (QTLs) for DM resistance have been detected in a limited number of cucumber accessions. In this study we applied genome-wide association analysis (GWAS) to detected genetic loci for DM resistance in a core germplasm (CG) of cucumber lines that represent diverse origins and ecotypes. Phenotypic data on responses to DM infection were collected in four field trials across three years, 2014, 2015, and 2016. With the resequencing data of these CG lines, GWAS for DM resistance was performed and detected 18 loci that were distributed on all the seven cucumber chromosomes. Of these 18 loci, only six (dmG1.4, dmG4.1, dmG4.3, dmG5.2, dmG7.1, and dmG7.2) were detected in two experiments, and were considered as loci with a stable effect on DM resistance. Further, 16 out of the 18 loci colocalized with the QTLs that were reported in previous studies and two loci, dmG2.1 and dmG7.1, were novel ones identified only in this study. Based on the annotation of homologous genes in Arabidopsis and pairwise LD correlation analysis, several candidate genes were identified as potential causal genes underlying the stable and novel loci, including Csa1G575030 for dmG1.4, Csa2G060360 for dmG2.1, Csa4G064680 for dmG4.1, Csa5G606470 for dmG5.2, and Csa7G004020 for dmG7.1. This study shows that the CG germplasm is a very valuable resource carrying known and novel QTLs for DM resistance. The potential of using these CG lines for future allele-mining of candidate genes was discussed in the context of breeding cucumber with resistance to DM.